Studi Meta Analisis Mengenai Absorbtive Capacity dan Inovasi - Indriartiningtias, Retno (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
This study focuses on the correlation between absorptive capacity and inovation. Most theories believe that absorptive capacity is positively correlated to inovation. However, a survey on 34 studies with total sample size of 19,529 shows a wide variation of the correlation coefficients, i.e. from -0.080 to 0.640. This study applies a meta-analysis on those 34 studies to find the true correlation of absorptive capacity and inovation. A procedure of sampling error correction and measurement error correction was carried out, and the result shows that the true correlation is between 0.026 and 0.694 with mean of 0.36, which is significantly positive on 95% confidence interval. Further analysis finds an indication that other variable influences the strength of the correlation, leads to an opportunity to conduct further specific meta-analysis studies.